(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Water is essential element required for the sustenance of life. Demand for drinking is increasing on continual basis with corresponding increasing population. This ever increasing demand can be fulfilled by designing efficient water distribution networks based on advance computing systems include modern hydraulic modeling . In present study water distribution network of Bakori region of Wagholi is designed which is located at district Pune, State Maharashtra, India. For the design of Bakori Phata water distribution network, study of present population, population of the three decades, daily water demand, flow characteristics and also survey of the village is done with help of digital GPS .Water distribution network for the villages is analyzed and designed with help of Bentleys WATERGEMS software.Water distribution network systems are designed to deliver water from a source in the adequate quantity, quality and at satisfactory pressure to all individual consumers. Water distribution network are designed with an objective of minimizing the overall cost while meeting the water demand requirements at adequate pressures. The system is a pipeline network consisting of one source node and several demand nodes is considered to find its optimal geometrical layout which delivers known demands from source to consumers over a long period of time.